2014
DOI: 10.1016/j.abb.2013.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Increased myocardial short-range forces in a rodent model of diabetes reflect elevated content of β myosin heavy chain

Abstract: Diastolic dysfunction is a clinically significant problem for patients with diabetes and often reflects increased ventricular stiffness. Attached cross-bridges contribute to myocardial stiffness and produce short-range forces, but it is not yet known whether these forces are altered in diabetes. In this study, we tested the hypothesis that cross-bridge-based short-range forces are increased in the streptozotocin (STZ) induced rat model of Type 1 diabetes. Chemically permeabilized myocardial preparations were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 41 publications
0
9
0
1
Order By: Relevance
“…In our study, MLC-2 phosphorylation did not differ among the groups and the lower MyBP-C phosphorylation in the vehicle-treated diabetic group was not significant. In contrast, Chung and colleagues [ 48 ] found that myocardial MLC-2 phosphorylation was significantly reduced in the early diabetic heart with no change in MyBP-C phosphorylation. However, Korte et al [ 49 ] have reported significant reductions in MyBP-C phosphorylation in the myocardium of diabetic swine.…”
Section: Discussionmentioning
confidence: 93%
“…In our study, MLC-2 phosphorylation did not differ among the groups and the lower MyBP-C phosphorylation in the vehicle-treated diabetic group was not significant. In contrast, Chung and colleagues [ 48 ] found that myocardial MLC-2 phosphorylation was significantly reduced in the early diabetic heart with no change in MyBP-C phosphorylation. However, Korte et al [ 49 ] have reported significant reductions in MyBP-C phosphorylation in the myocardium of diabetic swine.…”
Section: Discussionmentioning
confidence: 93%
“…Specifically, multidimensional minimization was used to fit the predicted force responses to tension-recovery records previously measured using myocardial preparations isolated from diabetic rats. These samples were useful for this analysis because, unlike most myocardial preparations from rodents, they only contained a single isoform of myosin heavy chain—in this case, the slower cycling β type ( Chung et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…As a result of this treatment, the myocardial samples contained only the β isoform of myosin heavy chain. Summary data describing the functional properties and the myosin heavy chain content of these preparations have been published ( Chung et al, 2013 ).…”
Section: Methodsmentioning
confidence: 99%
“…The streptozotosin (STZ) induced diabetes models utilizes the STZ toxin to damage pancreatic ß cells (Chung et al, 2014). It has been shown that under diabetic conditions, increased of lipid peroxidation and alters of antioxidant enzyme activities detected (Schmatz et al, 2012).…”
Section: Introductionmentioning
confidence: 98%